Rhizobacteria Mediate the Phytotoxicity of a Range of Biorefinery‐Relevant Compounds. (26th July 2019) - Herbert, Robin A.; Eng, Thomas; Martinez, Uriel; Wang, Brenda; Langley, Sasha; Wan, Kenneth; Pidatala, Venkataramana; Hoffman, Elijah; Chen, Joseph C.; Bissell, Mina J.; Brown, James B.; Mukhopadhyay, Aindrila; et al.
Abstract: Advances in engineering biology have expanded the list of renewable compounds that can be produced at scale via biological routes from plant biomass. In most cases, these chemical products have not been evaluated for effects on biological systems, defined in the present study as bioactivity, that may be relevant to their manufacture. For sustainable chemical and fuel production, the industry needs to transition from fossil to renewable carbon sources, resulting in unprecedented expansion in the production and environmental distribution of chemicals used in biomanufacturing. Further, although some chemicals have been assessed for mammalian toxicity, environmental and agricultural hazards are largely unknown. We assessed 6 compounds that are representative of the emerging biofuel and bioproduct manufacturing process for their effect on model plants ( Arabidopsis thaliana, Sorghum bicolor ) and show that several alter plant seedling physiology at submillimolar concentrations. However, these responses change in the presence of individual bacterial species from the A. thaliana root microbiome. We identified 2 individual microbes that change the effect of chemical treatment on root architecture and a pooled microbial community with different effects relative to its constituents individually. The present study indicates that screening industrial chemicals for bioactivity on model organisms in the presence of their microbiomes is important for biologically and ecologically relevant risk analyses. Environ Toxicol Chem 2019;38:1911–1922. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.